2012
DOI: 10.1186/1472-6920-12-25
|View full text |Cite
|
Sign up to set email alerts
|

The role of feedback in improving the effectiveness of workplace based assessments: a systematic review

Abstract: BackgroundWith recent emphasis placed on workplace based assessment (WBA) as a method of formative performance assessment, there is limited evidence in the current literature regarding the role of feedback in improving the effectiveness of WBA. The aim of this systematic review was to elucidate the impact of feedback on the effectiveness of WBA in postgraduate medical training.MethodsSearches were conducted using the following bibliographic databases to identify original published studies related to WBA and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 27 publications
3
122
0
8
Order By: Relevance
“…Even though this study had shown a promising result in term of students' improvement, systematic review had found that there is no direct effect between feedback and work-based assessments (Saedon et al 2012). There were few other factors that might be contributed to the result.…”
Section: Improvement In Students' Achievement In Mini-cexmentioning
confidence: 99%
“…Even though this study had shown a promising result in term of students' improvement, systematic review had found that there is no direct effect between feedback and work-based assessments (Saedon et al 2012). There were few other factors that might be contributed to the result.…”
Section: Improvement In Students' Achievement In Mini-cexmentioning
confidence: 99%
“…The aim of such WBAs tools is to not only provide evidence on a trainee's ability to perform in clinical practice but also some authors are of the view that it can show improvement in the quality of workplace training through supervised reflection and feedback. [5][6][7][8] This article is about the use of WBAs in improving trainee doctor's competence and workplace performance; explore why they are so unpopular amongst both trainees and trainers and what can be done to improve their work based learning.…”
Section: Introductionmentioning
confidence: 99%
“…10 There is good evidence that if well implemented, feedback from WBAs leads to a perceived positive effect on clinical practice. 11 However, there are very few studies in the literature evaluating the quality of the feedback provided to trainees during their WBAs, especially for medical specialties. We used accepted tools in educational research, such as qualitative analysis in the form of thematic analysis and also quantitative analysis .…”
Section: Evaluation Of Feedback Given To Trainees In Medical Specialtiesmentioning
confidence: 99%